Prevalence of the computed tomographic morphological DISSECT predictors in uncomplicated Stanford type B aortic dissection - Ante, Marius; Mylonas, Spyridon; Skrypnik, Denis; Bischoff, Moritz; Rengier, Fabian; Brunkwall, Jan; Böckler, Dittmar (European journal of vascular and endovascular surgery, 2018)
Objective/Background - The aim was to analyse the prevalence of computed tomographic (CT) morphological predictors and their influence on early chronic phase aortic diameter expansion in patients with uncomplicated acute Stanford type B aortic dissection (ATBAD). - Methods - This retrospective analysis reviewed the CT imaging of 140 patients admitted with uncomplicated ATBAD to two tertiary centres between March 2003 and April 2016. The prevalence of the following CT-morphological predictors was determined at baseline: primary entry tear (PET) diameter ≥ 10 mm, its location at the concavity of the aortic arch; maximum descending aortic diameter ≥ 40 mm; false lumen (FL) diameter ≥ 22 mm; partial FL thrombosis and a fusiform index (FI) of ≥0.64. Thoracic aortic diameter expansion (ADE) was evaluated in 65 patients treated by best medical therapy (BMT) (median CT follow up 11.6 months). Study end points were predictor prevalence and ADE. - Results - A mean ± SD of 2.45 ± 1.35 predictors were registered among all 140 patients; 75.0% of patients showed at least two predictors. In 7.9% of patients, no predictor was found. The prevalence of PET at the arch concavity was 18.6%, PET diameter ≥10 mm in 60.0%, maximal descending aortic diameter ≥40 mm in 51.4%, FL diameter ≥22 mm in 47.9%, partial FL thrombosis in 47.9%, and FI ≥ 0.64 in 20.7%. An ADE ≥5 mm was observed in 38 of 65 patients. Median observed ADE was 5.1 mm (median follow up (FU) 11.6 months, range −3.2-27.4 mm). Regression analysis for multiple predictors showed a basic ADE of 2.5 mm plus 1.9 mm per predictor at the median FU of 11.6 months (2.5 mm ± 1.9; 95% confidence interval CI -0.2-5.2 mm ± 0.7-3.0 mm; p = .003). - Conclusion - In the majority of patients, at least one of the investigated morphological predictors of disease progression in uncomplicated ATBAD was detected. An ADE ≥5 mm affected 38 of 65 BMT patients. CT based predictors help to define TBAD patients at risk of progression.